Comprehensive programme to promote a healthy lifestyle among employees of the fire and rescue service of the Republic of Sakha (Yakutia) in the context of family and professional activities - Ukolov, A.V.; Ponomarev, V.V.; Mogilevskaya, T.E.; Koksharov, E.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to justify and develop a comprehensive programme to support a healthy lifestyle for employees of the fire and rescue service of the Republic of Sakha (Yakutia) in the context of family and professional life, and to test it in practice. Methods and structure of the study. The study was conducted among employees of the fire and rescue service of the Republic of Sakha (Yakutia) in 2024. The sample size was 57 employees of the fire and rescue service and their family members. The following research methods were selected to ensure the correct organisation of the experimental work: analysis of scientific and methodological literature on the topic, interviews, questionnaires, surveys, pedagogical observations, expert assessment, systematisation, structuring, methods of mathematical statistics, experiments, etc. The preliminary theoretical and statistical material formed contributed to the development of a comprehensive programme to support a healthy lifestyle for employees of the fire and rescue service and their families and to test the innovation in practice. Results and conclusions. Upon completion of the pilot project, a comprehensive programme was developed to promote healthy lifestyles among employees of the fire and rescue services of the Republic of Sakha (Yakutia) in their family and professional lives. The comprehensive programme is adapted to the local climatic and geographical conditions of residence and the social and everyday life of employees in the industry and their families. The comprehensive programme includes three basic sections: physical education and health activities in the family; mass sporting events among employees' families; professional and practical classes and competitions among employees of the industry. The results of the experiment showed the high effectiveness of the experimental comprehensive programme, which was reflected in an average increase of 28% (P<0.05) in the healthy lifestyle indicators of employees of the fire and rescue industry and their families. All this allows us to recommend the developed comprehensive programme for promoting a healthy lifestyle for widespread use among the population of the Republic of Sakha.